2015
DOI: 10.1007/s13203-015-0127-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reaction variables on CO methanation process over NiO–La2O3–MgO/Al2O3 catalyst for coal to synthetic natural gas

Abstract: Reaction variables for methanation process were investigated using self-independently developed NiO-La 2 O 3 -MgO/Al 2 O 3 catalyst in a big lab scale reactor. The effects of reaction parameters, such as temperature, pressure, H 2 /CO flow ratio and space velocity on the activity of methanation catalyst were studied. 100 % CO conversion and 95 % of selectivity of methane can be achieved at 400°C and 3 MPa with the feed ratio of H 2 / CO as 3.25:1 and space velocity of 12,000 h -1 .The optimization reaction par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…SH 2-gas followed a decreasing trend with X Gly , indicating more hydrogen was consumed in alkane formation as conversion increased. A similar trend was reported by others, suggesting that CO hydrogenation was lowered at short contact times [50].…”
Section: Spent Catalysts Characterizationsupporting
confidence: 89%
“…SH 2-gas followed a decreasing trend with X Gly , indicating more hydrogen was consumed in alkane formation as conversion increased. A similar trend was reported by others, suggesting that CO hydrogenation was lowered at short contact times [50].…”
Section: Spent Catalysts Characterizationsupporting
confidence: 89%
“…Though the space velocity employed was calculated on the liquid flowrate basis, the gases (H 2 , CO, CO 2 ) flowed with the liquid stream. Therefore, the S H2 trend suggested that CO/CO 2 hydrogenation (producing hydrogen loss in the gas phase) were lessened by the short contact times [65]. Analogous to X gas , a decrease in hydrogen yield and selectivity to methane could be observed with WHSV, with a concomitant increase on CO and CO 2 .…”
Section: Effect Of Contact Timementioning
confidence: 95%
“…And the small active component Ni could improve the dispersion on the carrier. [17,25] H 2 -TPR analysis Figure 2 shows the H 2 -TPR profiles of the calcinated samples. Temperature range of reduction peak at 350-550 °C is attributed to the reduction of free NiO, i. e. α-NiO.…”
Section: Xrd Analysismentioning
confidence: 99%